De herói épico a herói trágico: uma análise da prática docente em cursinho popular - Welber de Barros Pinheiro (2023)
This paper is the outcome of a research-intervention that aimed to investigate what a teacher in a popular supplementary education course desire, given the precarious nature of teaching work, which could favor a possible subjective disimplication. Motivated by concerns and reflections arising from a previous intervention work, as well as the political and pedagogical significance of popular supplementary education courses, we sought, through offering a platform for expression, to enable teachers to freely discuss their experiences as educators in these courses. We structured our work in three stages: in the first stage, we conducted a literature review and data analysis, delving into the history, concepts, objectives, teacher training, experiences, and challenges of popular supplementary education courses. We also explored the contributions of psychoanalysis to the practice and training of teachers. In the second stage, we conducted clinical interviews with 22 teachers, representing our sample, to provide them with a space to freely discuss their experiences as educators in popular supplementary education courses. Finally, we developed clinical categories, derived from the interviews, to support the analysis of the interviews. Our literature review and theoretical foundation were based on two main theoretical and reflective axes. The first axis focused on exploring the field of popular supplementary education courses, investigating their history, challenges, and contradictions. In the second axis, we examined the contributions of psychoanalysis in teacher training, emphasizing its relevance in this context. We identified three fundamental gaps in this work: the possibility that popular supplementary education courses may inadvertently perpetuate the exclusion they aim to combat, student dropout as a symptomatic response to the imperative of inclusion, and the teacher's identification with both the student and the ideals of popular education. We observed how a teacher training program oriented toward psychoanalysis, in addition to discussions on the inherently exclusionary nature of any inclusion project, could contribute to strengthening the field of popular supplementary education courses.